O-GlcNAc: A Sweetheart of the Cell Cycle and DNA Damage Response - Liu, Caifei; Li, Jing (Frontiers in Endocrinology, 2018)
The addition and removal of O-linked N-acetylglucosamine (O-GlcNAc) to and from the Ser and Thr residues of proteins is an emerging post-translational modification. Unlike phosphorylation, which requires a legion of kinases and phosphatases, O-GlcNAc is catalyzed by the sole enzyme in mammals, O-GlcNAc transferase (OGT), and reversed by the sole enzyme, O-GlcNAcase (OGA). With the advent of new technologies, identification of O-GlcNAcylated proteins, followed by pinpointing the modified residues and understanding the underlying molecular function of the modification has become the very heart of the O-GlcNAc biology. O-GlcNAc plays a multifaceted role during the unperturbed cell cycle, including regulating DNA replication, mitosis and cytokinesis. When the cell cycle is challenged by DNA damage stresses, O-GlcNAc also protects genome integrity via modifying an array of histones, kinases as well as scaffold proteins. Here we will focus on both cell cycle progression and the DNA damage response, summarize what we have learned about the role of O-GlcNAc in these processes and envision a sweeter research future.